Immunoreactivity of Wilms tumor 1 (WT1) as an additional evidence supporting hemangiomatous rather than inflammatory origin in the etiopathogenesis of angiolymphoid hyperplasia with eosinophilia - Tokat, Fatma; Lehman, Julia S.; Dikicioglu Cetin, Emel; Sezer, Engin; Ince, Umit; Ozturk Durmaz, Emel (Dermatology Practical & Conceptual, 2018)
Background: Angiolymphoid hyperplasia with eosinophilia (ALHE) is a rare vascular proliferative disorder mainly located in the periauricular region. The etiopathogenesis of ALHE is unknown, and it is still controversial as to whether the entity represents a benign vascular neoplasm or an inflammatory process. Aim: Recently, the intracytoplasmic staining pattern of Wilms tumor 1 (WT1) on immunohistochemistry has highlighted true vascular neoplasms, such as microvenular hemangioma, tufted angioma, and spindle cell hemangioma, which has made it helpful to distinguish ALHE from vascular malformations, as there is a negative staining pattern in the other entities. We aimed to investigate the immunoreactivity of ALHE specimens for WT1 as well as glucose transporter protein 1 (GLUT1) immunohistochemistry, an important and sensitive marker for the diagnosis of infantile hemangioma, which recently has been described to label other hemangiomas, such as verrucous hemangioma. Material and methods: Clinical data and histopathological specimens from patients diagnosed with ALHE were reviewed, and immunohistochemical staining and microscopic analysis for WT-1 and GLUT1 were performed. Results: Intracytoplasmic endothelial staining of WT1 was detected in 19 of 20 ALHE specimens. GLUT1 was not detected in any ALHE specimen. Conclusions: We conclude that ALHE may represent a true hemangioma (i.e., benign vascular neoplasia) characterized by an eosinophil- and lymphocyte-rich inflammatory component as opposed to the reactive inflammatory dermatosis with a positive intracytoplasmic staining pattern for WT1. As far as we are aware, WT1 staining for ALHE has not been described to date.